Pengaruh Komunikasi Internal Dan Lingkungan Kerja Terhadap Kinerja Guru Dengan Kepemimpinan Transformasional Sebagai Variable Moderating Di SMKN 1 Bukittinggi - Dilla Puspita Zetri; Almasdi Almasdi (Jurnal Mirai Management, 2023)
The aim of this study is to investigate and analyze how Internal Communication and Working Environment affect Teacher Performance, with Transformational Leadership acting as a moderating factor at SMK Negeri 1 Bukittinggi. The research includes 123 teachers from SMK Negeri 1 Bukittinggi as participants. Data was collected through various methods, such as distributing questionnaires using Google Form, conducting interviews, and observations. The data was then analyzed using the SmartPLS 4.0 application. The findings indicate that: (1) Internal Communication has a positive and significant impact on Teacher Performance at SMK Negeri 1 Bukittinggi, (2) Working Environment also has a positive and significant impact on Teacher Performance at SMK Negeri 1 Bukittinggi, (3) Transformational Leadership negatively moderates the relationship between Internal Communication and Teacher Performance at SMK Negeri 1 Bukittinggi, and (4) Transformational Leadership positively moderates the relationship between Working Environment and Teacher Performance at SMK Negeri 1 Bukittinggi.